Reading to learn in chemistry ESP courses = Leer para aprender en cursos de Inglés con propósitos específicos, aplicación experimental del ciclo de andamiaje en la Facultad de Ciencias Químicas de la UNC - Ahumada, Luis Eduardo (2017)
The development of reading comprehension in a foreign language has been of concern to many applied linguists, who have proposed different approaches to enhance students’ comprehension. Scaffolding has been identified as one of the most effective teaching practices to enrich students’ reading comprehension. This study aims to test an adapted model of the Scaffolding Interaction Cycle (Martin and Rose, 2005) in the context of a reading comprehension course at the School of Chemistry, National University of Córdoba, in an attempt to help solve some of the main problems detected in the mainstream classroom approach, such as lack of understanding of reading strategies and of grammatical structures, and poor comprehension of semantically dense texts. A quasi-experimental study with no random assignment (one-group, pre- and post-test design) based on quantitative and qualitative methods to collect and analyse the data was conducted. In general, the results indicate that the instruction based on the adapted version of the Scaffolding Interaction Cycle contributes to enhancing the teaching of EFL reading and helps poor-skilled readers improve their reading comprehension skills. These results have pedagogical implications for reading courses addressed to non-native students who are studying English for Specific Purposes.